Augmented Reality Based Cultural Heritage in Improving Students' Literacy Culture in History Learning at SMK Muhammadiyah I Pekanbaru - Suroyo, Suroyo; Soedjiwo, Novena Ade Fredyarini; Entas, Derinta; Putra, Bima Maulana; Karimi, Amir; Soares, Antonio Constantino (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
History learning in vocational high schools (SMK) is often faced with challenges in increasing students' interest and understanding of culture and history. The application of Cultural Heritage-based Augmented Reality (AR) technology as an innovative solution in improving students' literacy culture in history learning at SMK Muhammadiyah I Pekanbaru. This study aims to evaluate the impact of using Cultural Heritage-based AR on historical understanding, cultural appreciation, and student interest at SMK Muhammadiyah I Pekanbaru. Experimental research method was used with one experimental group engaged in learning using Cultural Heritage-based AR and one control group following conventional learning. Data were collected through knowledge test, questionnaire, and observation. The results showed that the use of Cultural Heritage-based AR significantly improved students' historical understanding, cultural appreciation, and interest in SMK Muhammadiyah I Pekanbaru. Students who use AR technology find the learning experience more engaging and interacting, which results in a deeper understanding of culture and history. This research makes a significant contribution in the context of history education at SMK Muhammadiyah I Pekanbaru, that Cultural Heritage-based AR can be an effective tool to improve students' literacy culture. In addition, the application of this technology can also help preserve and promote local cultural and historical heritage